The effects of social isolation and the COVID-19 pandemic on air quality around the world - Duarte , Renata Lopes; Silva , Cláudio Paiva; Rocha, Cézar Henrique Barra (Electronic Journal "Fórum Ambiental da Alta Paulista", 2021)
In December 2019, a new virus variant was discovered in China, belonging to the coronavirus family, whose associated respiratory syndrome became known as COVID-19. Due to the ease of transmission, lethality and lack of knowledge about this new disease, several countries chose to adopt measures of social distancing, in addition to restrictions on travel and the performance of activities considered non-essential. Thus, the present study aimed to carry out a bibliographic survey about the main effects of social isolation on air quality, in some regions around the world, through consultation of scientific articles, national and international research institutes, as well such as satellite imagery. The results showed that the effects of these measurements were observed on air quality in different parts of the world, with a reduction in the levels of some of the main air pollutants, such as NO2, CO2, CO and particulate matter. In contrast, some studies showed that the concentration of O3 increased in certain regions. It was possible to conclude that the improvements observed were temporary, as they did not result from structural measures, but from transitory situations; and that the adoption of public policies to restrict the emission of pollutants is essential to reduce the incidence and aggravation of associated respiratory diseases, avoiding the overload of health systems, especially in the current pandemic scenario.